2017
DOI: 10.1186/s12966-017-0486-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors of physical activity among Chinese children and adolescents: a systematic review

Abstract: BackgroundLack of physical activity is a growing problem in China, due to the fast economic development and changing living environment over the past two decades. The aim of this review is to summarize the factors related to physical activity in Chinese children and adolescents during this distinct period of development.MethodsA systematic search was finished on Jan 10th, 2017, and identified 2200 hits through PubMed and Web of Science. English-language published studies were included if they reported statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 90 publications
(135 reference statements)
14
131
1
3
Order By: Relevance
“…Some other research in the Iranian context showed that physical activity, not unlike many other behavioral patterns, has a learning aspect and family can play a key role concerning this (Kazemi et al, 2011). In a systematic study, showed, in the Chinese context, that there existed a positive correlation between parents' model of physical activity and that of the children (Lu et al, 2017). Therefore, it is essential to attempt more to educate people and enculturate this issue in society especially among teenagers and youngsters who make the future of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Some other research in the Iranian context showed that physical activity, not unlike many other behavioral patterns, has a learning aspect and family can play a key role concerning this (Kazemi et al, 2011). In a systematic study, showed, in the Chinese context, that there existed a positive correlation between parents' model of physical activity and that of the children (Lu et al, 2017). Therefore, it is essential to attempt more to educate people and enculturate this issue in society especially among teenagers and youngsters who make the future of the country.…”
Section: Discussionmentioning
confidence: 99%
“…An excessive amount of sedentary behavior in adolescents is a growing problem in China (Lu et al, 2017). Although many factors may affect sedentary behavior, the association of smartphone use with sedentary behavior and leisure time is well demonstrated, much as sedentary behavior has been linked with traditional forms of screen-based activities (e.g., watching television, playing video games, and surfing the internet).…”
Section: Sedentary Behavior and Problematic Smartphone Usementioning
confidence: 99%
“…Moreover, student's PA behavior also be in uenced by others when they are in school and neighborhood, including others' support for PA or behaviors. The systematic review has revealed that students with physically active parents are more likely to have an active lifestyle [18], as well as peer support [19,20]. However, most of these studies were cross-sectional investigations.…”
Section: Page 3/23mentioning
confidence: 99%